1996
DOI: 10.1002/j.1460-2075.1996.tb00486.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a subdomain within DNA-(cytosine-C5)-methyltransferases responsible for the recognition of the 5′ part of their DNA target.

Abstract: In previous work on DNA‐(cytosine‐C5)‐methyltransferases (C5‐MTases), domains had been identified which are responsible for the sequence specificity of the different enzymes (target‐recognizing domains, TRDs). Here we have analyzed the DNA methylation patterns of two C5‐MTases containing reciprocal chimeric TRDs, consisting of the N‐ and C‐terminal parts derived from two different parental TRDs specifying the recognition of 5′‐CC(A/T)GG‐3′ and 5′‐GCNGC‐3′. Sequences recognized by these engineered MTases were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…From the protein side, a conserved arginine is responsible for the recognition of the guanine 5 to the target cytosine. These shared recognition patterns may be common to other 5mC methyltransferases recognizing a guanine 5 to the target base (27,28).…”
Section: Haeiii Dna Methyltransferasementioning
confidence: 87%
“…From the protein side, a conserved arginine is responsible for the recognition of the guanine 5 to the target cytosine. These shared recognition patterns may be common to other 5mC methyltransferases recognizing a guanine 5 to the target base (27,28).…”
Section: Haeiii Dna Methyltransferasementioning
confidence: 87%
“…X-ray structures of reaction complexes for two C5-MTases (M.HhaI G C GC and M.HaeIII GG C C) are available to date (12,13), which revealed that a target DNA sequence is recognized via two recognition loops located in the TRD; the 5′ part of the target site (on the target strand) is contacted by the N-terminal recognition loop (Loop 1), whereas the 3′ part of target sequence is recognized by Loop 2 (Figure 1). Attempts to create enzymes with novel specificities by recombining loop regions among multi-specific (14) or mono-specific (15) C5-MTases showed that changes in the recognition Loop 1 always lead to inactive enzymes, whereas changes in Loop 2 were often tolerated, but yielded enzymes with diminished catalytic activity and degenerate target specificity. The specificity of the chimeric MTases typically resembled the sequence defined by Loop 1.…”
Section: Discussionmentioning
confidence: 99%
“…Crystal structures of M.HhaI (12) and M.HaeIII (13) show that these enzymes recognize their targets via two distinct recognition loops (Loops 1 and 2) which form multiple base-specific contacts with two distinct segments of their target sequences (Figure 1). Modular organization of TRDs themselves suggested that novel specificities could potentially be created by swapping loop regions between different MTases, however, such experiments typically yielded enzymes with diminished catalytic activity and relaxed target specificity (14,15). During earlier work on swapping segments of TRD between monospecific DNA C5-MTases we found that hybrid MTases, in which the C-terminal recognition loop (Loop 2) of M.HhaI was exchanged, often retained the ability to methylate DNA although with lower efficiency (15).…”
Section: Introductionmentioning
confidence: 99%
“…In their natural context with other TRDs, however, some mutations of amino acids, located outside the TRD itself but in its vicinity, have been found to modulate the activity of the TRD (Figure 2) in cases where TRDs abut with each other. Genetic evidence for such recognition is provided in the accompanying paper (Lange et al, 1996). Again structural analyses with multispecific MTases must be performed to understand the molecular basis of this modulation.…”
Section: Discussionmentioning
confidence: 99%